2013
DOI: 10.3390/ijms14036205
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Analysis of Secretory Immunoglobulin A (sIgA) Expression in Plants

Abstract: Delivery of secretory immunoglobulin A (sIgA) to mucosal surfaces as a passive immunotherapy agent is a promising strategy to prevent infectious diseases. Recombinant sIgA production in plants requires the co-expression of four transcriptional units encoding the light chain (LC), heavy chain (HC), joining chain (JC) and secretory component (SC). As a way to optimize sIgA production in plants, we tested the combinatorial expression of 16 versions of a human sIgA against the VP8* rotavirus antigen in Nicotiana b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
4
27
1
Order By: Relevance
“…Estimated expression level of both IgA1 and IgA2 was 25-23 mg/ kg fresh leaf weight, a yield almost five times lower than that obtained for the chimeric 2G8 IgG1 version (120 mg/kg), using the same transient expression system. These crude yields are consistent with those previously reported by others for an IgA against the rotavirus VP8 (31.6 mg/kg fresh weight) or for the anti-GP120 SIgA 2G12 produced in N. benthamiana (25 mg/kg fresh weight) (Juarez et al, 2013;Paul et al, 2014). It is worth to notice that this latter IgA in its IgG1 version accumulated up to 100 mg/kg in agroinfiltrated leaves (Rosenberg et al, 2013), paralleling the remarkable difference in yield observed between the IgG and the IgA version of our 2G8 Ab.…”
Section: Discussionsupporting
confidence: 91%
“…Estimated expression level of both IgA1 and IgA2 was 25-23 mg/ kg fresh leaf weight, a yield almost five times lower than that obtained for the chimeric 2G8 IgG1 version (120 mg/kg), using the same transient expression system. These crude yields are consistent with those previously reported by others for an IgA against the rotavirus VP8 (31.6 mg/kg fresh weight) or for the anti-GP120 SIgA 2G12 produced in N. benthamiana (25 mg/kg fresh weight) (Juarez et al, 2013;Paul et al, 2014). It is worth to notice that this latter IgA in its IgG1 version accumulated up to 100 mg/kg in agroinfiltrated leaves (Rosenberg et al, 2013), paralleling the remarkable difference in yield observed between the IgG and the IgA version of our 2G8 Ab.…”
Section: Discussionsupporting
confidence: 91%
“…We showed that vacuolar variants of the mAb14D9 accumulated at levels 10‐ to 15‐folds higher than secretory forms. Although ER retention increased antibody yields in some cases (Juarez et al ., ; Ko et al ., ; Petruccelli et al ., ; Schouten et al ., ), accumulation of Ig sorted to central vacuole in leaves has not been previously reported. Only one report compared apoplast and vacuolar accumulation of mAbs in carrot cell suspension culture, and the highest yield was obtained for secreted forms of human IgG 1 and IgG 4 (Shaaltiel et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Despite this difference, the production volume of S-hyIgA was 8.0 μg/g fresh weight and that of dimeric hyIgA was 11 μg/g25. Although directing to other antigens, other studies revealed that SIgA production was 15.2 μg/g in transgenic Tobaccos11 and that transient Nicotiana benthamiana produced SIgA ranging from 25 μg/g to 32.5 μg/g1112. The in vitro neutralization activities of our S-hyIgA and dimeric hyIgA against Stx1 were similar based on IgA concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…Although there have been several reports, the production of SIgA in a single mammalian cell is still challenging78. The first report of SIgA production using a plant expression system was earlier than that as to a mammalian cell system, and such reports on plant systems have recently been increasing9101112. A plant expression system has advantages as to oral passive immunity due to the ability of oral administration without or with minimal formulation when edible plant hosts are used13.…”
mentioning
confidence: 99%